Standardization of a fluorimetric assay for the determination of tissue angiotensin-converting enzyme activity in rats - Oliveira,E.M. (2000)
The tripeptide Hip-His-Leu was used to standardize a fluorimetric method to measure tissue angiotensin-converting enzyme (ACE) activity in rats. The fluorescence of the o-phthaldialdehyde-His-Leu adduct was compared in the presence and absence of the homogenate (25 µl) to determine whether the homogenate from different tissues interfered with the fluorimetric determination of the His-Leu product. Only homogenates from lung and renal medulla and cortex showed significantly altered fluorescence intensity. To overcome this problem, the homogenate from these tissues were diluted 10 times with assay buffer. The specificity of the assay was demonstrated by the inhibition of ACE activity with 3 µM enalaprilat (MK-422). There was a linear relationship between product formation and incubation time for up to 90 min for homogenates of renal cortex and medulla and liver, for up to 60 min for ventricles and adrenals and for up to 30 min for the aorta, lung and atrium homogenates. In addition, there was a linear relationship between product formation and the amount of protein in the homogenates within the following range: lung, 30-600 µg; renal cortex and medulla, 40-400 µg; atrium and ventricles, 20-200 µg; adrenal, 20-100 µg; aorta, 5-100 µg; liver, 5-25 µg. No peptidase activity against the His-Leu product (31 nmol), assayed in borate buffer (BB), was detected in the different homogenates except the liver homogenate, which was inhibited by 0.1 mM r-chloromercuribenzoic acid. ACE activity in BB was higher than in phosphate buffer (PB) due, at least in part, to a greater hydrolysis of the His-Leu product in PB. ACE activity of lung increased 20% when BB plus Triton was used. Enzyme activity was stable when the homogenates were stored at -20o or -70oC for at least 30 days. These results indicate a condition whereby ACE activity can be easily and efficiently assayed in rat tissue samples homogenized in BB using a fluorimetric method with Hip-His-Leu as a substrate.